2014
DOI: 10.1080/00131881.2014.965569
|View full text |Cite
|
Sign up to set email alerts
|

Easy, collaborative and engaging – the use of cloud computing in the design of management classrooms

Abstract: Background: Cloud computing has recently received interest in information systems research and practice as a new way to organise information with the help of an increasingly ubiquitous computer infrastructure. However, the use of cloud computing in higher education institutions and business schools, as well as its potential to create novel learning environments remains an underresearched topic. Purpose: To address the research gap, this paper investigates how the capabilities of cloud computing have fostered c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 79 publications
0
10
0
Order By: Relevance
“…It is necessary to create certain standards and criteria for the implementation of e-learning. Schneckenberg (2014) emphasised that the increased interest in the field of cloud technologies stimulates a large amount of research. Various methods of presenting information using computer appear.…”
Section: Introductionmentioning
confidence: 99%
“…It is necessary to create certain standards and criteria for the implementation of e-learning. Schneckenberg (2014) emphasised that the increased interest in the field of cloud technologies stimulates a large amount of research. Various methods of presenting information using computer appear.…”
Section: Introductionmentioning
confidence: 99%
“…According to the results, participants think that cloud services may have benefits on connection and collaborative work with various people. In a similar study in which students' views are observed, it is revealed that in a classroom designed by cloud computing, students enjoy with informal learning and communication; their encouragement, academic engagement and individual and group learning skills are improved (Schneckenberg, D. 2014). In virtual environment based on cloud computing created for students who study in a field which requires application in real environments is more secure, cost effective and flexible environment which allows working in situations that may be impossible in reality collaboratively (Jalali, M., Bouyer, A., Arasteh, B., & Moloudi, M. 2013).…”
Section: Discussion and Suggestionsmentioning
confidence: 99%
“…Some papers have proposed tailor-made or bespoke architectures for specific requirements, (5/52) [143], [144], [162], [163], [165]. Other papers have outlined general infrastructure ideas in education (5/52) [142], [154], [166], [168], [170], whereas other researchers have discussed the ideas of collaborative learning and use of application software to support these ideas (5/52) [131], [150], [153], [179], [180]. In addition to studies highlighted above (14/52) [133]- [136], [138], [139], [146], [149], [152], [155], [157], [160], [176], [177], certain articles have included an ''evaluation model'' [134], sustainable ICT provisions [149], and an information management system structure based wholly on CC technologies [136].…”
Section: ) Existing Proposals Of Framework To Develop and Operate Cmentioning
confidence: 99%